The Effectiveness Of Betel Leaf Boiled Water And Snakehead Fish Consump-tion Against Wound Healing Perineum In Postpartum Mothers - Ita Herawati; Dita Putri Allawiyana (International Journal of Health and Pharmaceutical (IJHP), 2023)
Childbirth often results in birth canal injuries. Perineal injuries are found in about 70% of mothers who give birth due to inability of the muscles and soft tissue of the pelvis during the baby's birth. The process of healing perineal wounds has a healing time that varies, namely 6-7 days, and is influenced by several things such as the characteristics of the mother giving birth, nutritional status, treatment and condition of the wound. One of the effects of delayed perineal wound healing is the occurrence of infection, prevention of infection can be done with pharmacological and non-pharmacological treatment. To find out how the effectiveness of betel leaf decoction and consumption of snakehead fish on the healing of perineal wounds in postpartum mothers.The research design used was a literature review (journal review). Journals used as data include systematic search studies of databases and interventions for respondents. The results of a journal review of 10 data used as references state that consumption of snakehead fish is proven to be used as a non-pharmacological treatment for postpartum wound healing. Similarly, boiled betel leaf water which is used as a treatment for birth canal injuries has been shown to accelerate the healing of perineal wounds.